Z problematyki prawa celnego - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1983)
The article discusses several problems from the domain of duty — legislation. It presents such questions as: the notion of duties and their resemblance to taxes. The author claims, that duties are in fact taxes. The problems further discussed in this article are duties collected in commercial and non-commercial turnover. What has been characterized in greater detail are the differences between these two kinds of duties, particularly those concerning their assessment and amount. The author critically evaluates the distinction made between these two. kinds of duties. He claims, that the division into commercial and non-commercial duty is artificial and does not consider economic realities. Therefore, the author is for the abolition of this division. The duties, which are collected from tourists, the so-called non-commercial duties, have also been criticised in the article. In the author's opinion, the integration of socialist countries requires among others free flow of people. Meanwhile, however, the existing duties constitute one of the restraints of the development of tourism. Moreover, in the socialist countries, too much importance is attached ' to duties as instruments forming the market balance. It seems to be a task trespassing the possibilities of duties as such. Duties applied to the flow of tourists are also to limit the exportation of foreign currency. And yet, the really necessary move is the introductioin of a possibility to exchange ' the currency of socialist countries, using at the same time, such rates of exchange which consider the purchasing power of population. The author believes, that it would be highly advisable to abolish such duties in the tourist exchange among Comecon countries.
From the duty issue